A comparative study of socio demographic and clinical characteristics of heroin injectors and heroin chasers: a comparative study done in a tertiary care de-addiction center of Kashmir, India - Mir, Zoya; Preetkamal; Rather, Yasir Hassan (International Journal of Research in Medical Sciences, 2025)
Background: Heroin use has intensified into a major public health concern in Kashmir, accompanied by a rising prevalence of high-risk routes of administration, particularly injecting. However, regional research comparing injectors and chasers remains scarce. This study examined the socio-demographic and clinical differences between heroin injectors, heroin chasers, and healthy controls in a tertiary de-addiction centre in Kashmir. Methods: A cross-sectional comparative study was conducted among 50 heroin injectors, 50 heroin chasers, and 30 healthy controls recruited through purposive sampling. Participants aged ≥18 years meeting DSM-5 criteria for Opioid Use Disorder were assessed after withdrawal stabilization using a semi-structured socio-demographic and clinical questionnaire. Data analysis was performed in SPSS-21 using descriptive statistics, chi-square tests, and independent t-tests, with statistical significance set at p<0.05. Results: Injectors were significantly younger, less educated, and more frequently engaged in unskilled or unstable occupations than chasers and controls (p<0.001). Injectors showed earlier onset of heroin use, longer illness duration, and more treatment attempts. Both groups had comparable legal involvement (25%). High-risk behaviors were far more common among injectors: 80% reused needles, 72% shared needles, 50% were hepatitis-positive, and 34% reported overdose. Medical complications such as abscesses and skin infections occurred only among injectors. Conclusions: Heroin injectors represent a high-risk subgroup with greater addiction severity and substantially elevated medical and behavioural harms. These findings highlight the need for targeted harm-reduction interventions, early identification of injecting-related risks, and preventive strategies to reduce transition from chasing to injecting within the Kashmir region.